Kami and the yaks - Stryer, Andrea Stenn, 1938-; Dodson, Bert (Palo Alto, Calif. : Bay Otter Press, 2007)
In the Himalaya Mountains of Nepal, Kami, a deaf Sherpa boy, braves a fierce storm to lead his father and brother to their family's lost yak herd.
Schneider Family Book Award, Young Children, 2008.
Keywords: Sherpa (Nepalese people) -- Himalaya Mountains -- Juvenile fiction; Deaf children -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Himalaya Mountains -- Juvenile fiction; Deaf people -- Fiction; People with disabilities -- Fiction; Sherpa (Nepalese people) -- Fiction; Yak -- Fiction; Nepal -- Fiction; Himalaya Mountains -- Fiction; Fathers and sons -- Fiction